Electric vehicles and power quality in low voltage networks: Real data analysis and modeling - (:unkn) unknown (Elsevier, 2022)
Electric vehicles (EVs) will help to decarbonize energy systems. However, their connection to on-board level 2 chargers (7.2 kW) at household facilities brings challenges to Distribution Network Operators (DNOs) as they can affect the power quality of low voltage (LV) networks. In order to truly assess these effects, the electrical behavior of the on-board charger in terms of its non-linear content, power demand, and charge rate must be understood first. Nonetheless, most modeling methodologies with this aim result in circuital approaches, and thus, in heavy computational burdens, or assume simplified representations that do not correspond to the reality of the charge. To overcome this, we present a new methodology to model the power quality characteristics of EVs based on measured data from the harmonic spectra of the charger. The model provides a precise and efficient electrical characterization, where probabilistic models of the harmonic spectra are used to compute the power demand during every stage of the charge. Due to its probabilistic nature, these harmonic spectra are represented using Gaussian Mixture Models. We validate the model contrasting simulated data versus real measured one. Then, we illustrate a case study of the model in a LV network power quality assessment with different EV penetration levels, considering time-series harmonic power flows with 10-min resolution under a Monte Carlo approach. Obtained results revealed an increase in the network chargeability and voltage unbalance, along with an increased content of the third harmonic, which appears to be the most intense.

Los vehículos eléctricos (EV) ayudarán a descarbonizar los sistemas energéticos. Sin embargo, su conexión a cargadores de nivel 2 a bordo (7,2 kW) en las instalaciones domésticas presenta desafíos para los operadores de redes de distribución (DNO), ya que pueden afectar la calidad de la energía de las redes de baja tensión (BT). Para evaluar realmente estos efectos, primero se debe entender el comportamiento eléctrico del cargador integrado en términos de su contenido no lineal, demanda de energía y tasa de carga. No obstante, la mayoría de las metodologías de modelado con este objetivo resultan en enfoques circuitales y, por lo tanto, en pesadas cargas computacionales, o asumen representaciones simplificadas que no corresponden a la realidad de la carga. Para superar esto, presentamos una nueva metodología para modelar las características de calidad de la energía de los vehículos eléctricos en función de los datos medidos de los espectros armónicos .del cargador El modelo proporciona una caracterización eléctrica precisa y eficiente, donde se utilizan modelos probabilísticos de los espectros armónicos para calcular la demanda de energía durante cada etapa de la carga. Debido a su naturaleza probabilística, estos espectros armónicos se representan mediante modelos de mezcla gaussiana . Validamos el modelo contrastando datos simulados versus medidos reales. Luego, ilustramos un caso de estudio del modelo en una evaluación de la calidad de la energía de una red de LV con diferentes niveles de penetración de EV, considerando flujos de energía armónicos de series temporales con una resolución de 10 minutos bajo un enfoque de Monte Carlo . Los resultados obtenidos revelaron un aumento en la capacidad de carga de la red y el desequilibrio de voltaje, junto con un mayor contenido del tercer armónico, que parece ser el más intenso.
Keywords: Automóviles eléctricos; Electric automobiles; Vehículos eléctricos; Electric vehicles; Electric vehicles; Análisis de redes eléctricas; Electric network analysis; Power quality; Electric vehicle